PSYCHOLOGICAL ASPECTS OF THE COMPETENCY-BASED APPROACH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This article analyzes the theoretical and practical foundations of the competency-based approach in personnel management. The transition from the traditional job analysis method to the concept of competency modeling is described. The content of the concepts of competence and competency, their differences, and interpretations within different scientific schools (British, American, and Russian approaches) are examined. Competency models are considered based on individual, group, and universal approaches, and their advantages and disadvantages are compared. In addition, the universal model proposed by A. V. Ovchinnikov and the “Great Eight” competency model developed by SHL are described. The article reveals organizational and methodological aspects of developing, implementing, and assessing competency models. The research findings substantiate the importance of the competency-based approach in personnel selection, evaluation, and development processes.